A natural antiviral and immunomodulatory compound with antiangiogenic properties - Bueno, Carlos Alberto (2012)
Meliacine (MA), an antiviral principle present in partially purified leaf extracts of Melia azedarach L., reduces viral load and abolishes the inflammatory reaction and neovascularization during the development of herpetic stromal keratitis in mice. 1-cinnamoyl-3,11-dihydroxymeliacarpin (CDM), obtained from MA, displays anti-herpetic and immunomodulatory activities in vitro. We investigated whether CDM interferes with the angiogenic process. CDM impeded VEGF transcription in LPS-stimulated and HSV-1-infected cells. It proved to have neither cytotoxic nor antiproliferative effect in HUVEC and to restrain HUVEC migration and formation of capillary-like tubes. Moreover, MA inhibits LMM3 tumor-induced neovascularization in vivo. We postulate that the antiangiogenic activity of CDM displayed in vitro as a consequence of their immunomodulatory properties is responsible for the antiangiogenic activity of MA in vivo, which would be associated with the lack of neovascularization in murine HSV-1-induced ocular disease. Highlights ► 1-cinnamoyl-3,11-dihydroxymeliacarpin (CDM) restrains angiogenesis in vitro. ► CDM disrupts tubule formation in vitro because it modulates cytokine production. ► CDM antiangiogenic activity explains the improvement of murine herpetic keratitis. ► This triterpenoid might be an excellent candidate as a novel anti-herpetic agent.